(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
Possibility of using of inorganic sorbent ion-exchanger argyllizite for thin-layer chromatographic separation of rare elements’ ions (rhenium, molybdenum, vanadium, tungsten) using mixtures of ethanol with different acid and bases solutions as mobile phase has been studied. It has been estimated that mobile phase content and concentration of its components influence considerably on migration properties of separated ions. The presence of ethanol in the mobile phase creates possibility for regulation of ions mobility and secures compactness of ions’ pots on thin layers. It has been shown that argyllizite fixed thin layers can be used successfully for separation of micro-amounts of ions of rare elements. New versions for separation of multi-component mixtures of above-mentioned ele-ments have been elaborated.